2021
DOI: 10.1016/j.abd.2020.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Case for diagnosis. Erythematous and infiltrated plaques in the infrahyoid region

Abstract: Leprosy is a chronic infectious disease caused by Mycobacterium leprae and, depending on the host immune status, presents different clinical forms. This report describes the case of a 46-year-old man who had hypoesthetic lesions in the infrahyoid region for 30 days. The bacilloscopy was negative. The anatomopathological examination showed alterations corresponding to the tuberculoid pole (epithelioid histiocytes) and virchowian pole (foamy histiocytes), compatible with borderline-virchow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
1
0
1
Order By: Relevance
“…Regarding the treatment of leprosy patients co-infected with HIV, studies highlight complexities and challenges. It was observed that infection with this virus does not seem to change the incidence or clinical spectrum of the disease, and does not cause changes, or does so discreetly, in the course of leprosy [ 22 , 23 ]. Therefore, the symptoms, reactions and impact of ART and PREP are uncertain in cases of HIV/Leprosy, making it difficult for the patient to adhere to available treatment [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the treatment of leprosy patients co-infected with HIV, studies highlight complexities and challenges. It was observed that infection with this virus does not seem to change the incidence or clinical spectrum of the disease, and does not cause changes, or does so discreetly, in the course of leprosy [ 22 , 23 ]. Therefore, the symptoms, reactions and impact of ART and PREP are uncertain in cases of HIV/Leprosy, making it difficult for the patient to adhere to available treatment [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…A coinfecção entre o vírus HIV e a Hanseníase ainda não possui seus mecanismos de evolução completamente elucidados, porém nota-se que a infecção pelo HIV não provoca alterações, ou as faz discretamente, no curso da hanseníase (Bezerra et al, 2021), entretanto, as reações hansênicas do tipo 1 foram relacionadas ao início do tratamento com Terapia Antirretroviral (TARV) (Torreão, 2020). Sendo assim, os sintomas, as reações e o impacto da TARV são incertos nos casos de HIV/Hanseníase, de maneira a dificultar a adesão do enfermo ao tratamento disponível (Maia, 2019).…”
Section: Introductionunclassified